Analisis Dinamika Market Saturation dan Turnover pada Bisnis Coffeeshop di Kawasan Aniva Grande Gading Serpong - Jasson Lorencius; Budi Setiawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The rapid growth of the coffee shop industry in the Aniva Grande area, Gading Serpong, has led to intense market saturation and a high rate of business turnover. This condition challenges the sustainability of businesses and requires a deep understanding of its root causes. Therefore, this study aims to analyze the systemic dynamics behind market saturation and turnover, and to identify the driving factors through the Structure-Conduct-Performance (SCP) theoretical framework.This research employs a systematic literature review of 50 relevant sources, including scientific journals, books, and industry reports. The data were analyzed qualitatively to map the cause-and-effect relationships between market structure, the collective conduct of business actors, and the resulting market performance.The analysis reveals that the primary issue is not merely competition, but a crisis of differentiation that triggers mimetic isomorphism. A market structure with low barriers to entry (Structure) encourages business actors to imitate one another (Conduct), which in turn creates a homogeneous market. The Performance resulting from these dynamics includes consumer perception of saturation and choice fatigue, as well as suppressed profitability and a high turnover rate that functions as a natural selection mechanism for businesses. This process is accelerated by external pressures such as price competition and rental costs, as well as internal weaknesses like limited managerial capabilities.